Epidemiology and Molecular Characterization of Streptococcus pyogenes Recovered from Scarlet Fever Patients in Central Taiwan from 1996 to 1999 - Chiou, Chien-Shun (American Society for Microbiology, 2004)
One hundred seventy-nine Streptococcus pyogenes isolates recovered from scarlet fever patients from 1996 to 1999 in central Taiwan were characterized by emm, Vir, and pulsed-field gel electrophoresis (PFGE) typing methods. The protocols for Vir and PFGE typing were standardized. A database of the DNA fingerprints for the isolates was established. Nine emm or emm-like genes, 19 Vir patterns, and 26 SmaI PFGE patterns were detected among the isolates. Among the three typing methods, PFGE was the most discriminatory. However, it could not completely replace Vir typing because some isolates with identical PFGE patterns could be further differentiated into several Vir patterns. The prevalent emm types were emm4 (n = 81 isolates [45%]), emm12 (n = 64 [36%]), emm1 (n = 14 [8%]), and emm22 (n = 13 [7%]). Some emm type isolates could be further differentiated into several emm-Vir-PFGE genotypes; however, only one genotype in each emm group was usually predominant. DNA from nine isolates was resistant to SmaI digestion. Further PFGE analysis with SgrAI showed that the SmaI digestion-resistant strains could be derived from indigenous strains by horizontal transfer of exogenous genetic material. The emergence of the new strains could have resulted in an increase in scarlet fever cases in central Taiwan since 2000. The emm sequences, Vir, and PFGE pattern database will serve as a basis for information for the long-term evolutionary study of local S. pyogenes strains.